The use of prepositions among malay adult ESL learners - Sudhakaran, Beena (2008)
One predicament facing an educationist is whether grammar should be taught formally, or allowed to be naturally acquired. This question is pertinent in the face of the fact that there has generally been a deterioration of students‟ grammar skills among English as a second language (ESL) learners in Malaysia, especially in the use of syntactical categories such as prepositions and articles.In order to get to the depth of the issue, a protracted study using a case study research design was carried out. This study was carried out on seven Malay students from the International Islamic University Malaysia. The study sought to determine the extent to which students acquired English prepositions in the naturalistic setting in the oral and written modes, the different types of errors in students‟ use of prepositions, in the use of alternative locative frames, and whether there was a specific pattern in acquisition of prepositions. Data from students‟ written samples, interviews and presentations were collected. The baseline data was collected initially, and subsequent data collected at six monthly intervals over three years. The progress of the students was monitored over this period. An analysis of students‟ use of prepositions in the various speaking and writing tasks was carried out. Although errors persist, most subjects showed improvements in their use of prepositions for both speaking and writing tasks. The errors they committed were of two kinds: errors of commission and errors of omission. They had more errors of commission than errors of omission. In the use of alternative locative frames, one of the most common errors was the unnecessary use of the phrase involving a preposition, „for me‟. Persistent errors could arise due to incomplete linguistic rule formation. It also cannot be denied that there could be transfer from the students‟ first language (L1). There were also instances of other words like adverbs being used instead of prepositions. With respect to the performances of students in the most commonly used prepositions, and in certain clusters of prepositions, in the speaking tasks, the best improvement was seen in the prepositions „for‟, „in‟ and „about‟, while in the writing tasks, the prepositions „to, „of‟ and „in‟ were among those where the students had the best results. These findings imply that grammar should be taught in a way that is compatible with the natural processes of acquisition. The subjects‟ overall competency was not of a very high level, not having gained native use of the various prepositions. Consequently, language instructors should also be equipped with special skills to be able to teach prepositions; they should be provided with suitable, accurate teaching materials. Learners should also be developmentally ready to acquire prepositions, and changes have to be made in the curriculum for instruction of prepositions that pose greater problems to second language (L2) learners.